2022
DOI: 10.3389/fendo.2022.849076
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potential Biomarkers for Postmenopausal Osteoporosis Based on Untargeted GC/LC-MS

Abstract: PurposeAs an important public health problem, osteoporosis (OP) in China is also in an upward trend year by year. As a standard method for diagnosing OP, dual-energy X-ray absorptiometry (DXA) cannot analyze the pathological process but only see the results. It is difficult to evaluate the early diagnosis of OP. Our study was carried out through a serum metabolomic study of OP in Chinese postmenopausal women on untargeted gas chromatography (GC)/liquid chromatography (LC)–mass spectrometry (MS) to find possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Studies have now shown the presence of biomarkers in the OP, such as some potential biomarkers of OP that have been found in metabolomics studies. These metabolites are mainly concentrated in fats and amino acids [ 9 ]. Studies have shown that circulating miR-181c-5p and miR-497-5p may serve as potential biomarkers to monitor the effect of anti-OP therapy or diagnostic methods [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have now shown the presence of biomarkers in the OP, such as some potential biomarkers of OP that have been found in metabolomics studies. These metabolites are mainly concentrated in fats and amino acids [ 9 ]. Studies have shown that circulating miR-181c-5p and miR-497-5p may serve as potential biomarkers to monitor the effect of anti-OP therapy or diagnostic methods [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the model group, the levels of lactate, citrate, and succinate in the sAB-, ABP-, and sABP-treated groups were decreased. This phenomenon can be explained by the bone resorption of osteoclasts consuming a large amount of energy, which causes the speed up of glycolysis and oxidative phosphorylation [ 24 ]. With the enhancement of energy metabolism, the tricarboxylic acid cycle (TCA) is also enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Third-generation alendronate tablets can act on the competitive target of OC to inhibit OC activity and play a role in maintaining bone structure, improving bone mineralisation and bone density [7]. Nonetheless, it is imperative to consider the potential risks of osteonecrosis of the jaw [8] and gastrointestinal discomfort [9] linked to the administration of alendronate tablets in the management of patients with PMOP. Regular assessments of both e cacy and safety are crucial.…”
Section: Introductionmentioning
confidence: 99%